2021
DOI: 10.1093/molbev/msab081
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Phylogenetic Analysis of the Serpin Superfamily

Abstract: Serine protease inhibitors (serpins) are found in all kingdoms of life and play essential roles in multiple physiological processes. Owing to the diversity of the superfamily, phylogenetic analysis is challenging and prokaryotic serpins have been speculated to have been acquired from Metazoa through horizontal gene transfer (HGT) due to their unexpectedly high homology. Here we have leveraged a structural alignment of diverse serpins to generate a comprehensive 6000-sequence phylogeny that encompasses serpins … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 89 publications
2
48
0
Order By: Relevance
“…Thus, an alternative hypothesis was proposed suggesting that serpins constitute an ancient superfamily that firstly appeared in prokaryotes prior to divergent evolution [ 120 ]. This hypothesis was supported by a recent phylogenetic analysis using 6000 non-redundant sequences that encompass serpins from all living kingdoms [ 124 ]. It was reported that most microbial serpins belong to two main groups (T and U), where a large proportion exhibits a predicted inhibitory function [ 124 ].…”
Section: Serpins Natural Inhibitors To Control the Activity Of Serine Proteasesmentioning
confidence: 82%
See 4 more Smart Citations
“…Thus, an alternative hypothesis was proposed suggesting that serpins constitute an ancient superfamily that firstly appeared in prokaryotes prior to divergent evolution [ 120 ]. This hypothesis was supported by a recent phylogenetic analysis using 6000 non-redundant sequences that encompass serpins from all living kingdoms [ 124 ]. It was reported that most microbial serpins belong to two main groups (T and U), where a large proportion exhibits a predicted inhibitory function [ 124 ].…”
Section: Serpins Natural Inhibitors To Control the Activity Of Serine Proteasesmentioning
confidence: 82%
“…This hypothesis was supported by a recent phylogenetic analysis using 6000 non-redundant sequences that encompass serpins from all living kingdoms [ 124 ]. It was reported that most microbial serpins belong to two main groups (T and U), where a large proportion exhibits a predicted inhibitory function [ 124 ].…”
Section: Serpins Natural Inhibitors To Control the Activity Of Serine Proteasesmentioning
confidence: 82%
See 3 more Smart Citations